Região da Jabotiana, anos 2000 : história e discurso no processo de nomeação - Cruz, Eluzia Lisboa da (2016)
The Jabotiana is located in the west of Aracaju- SE. It is an urban and at the same time rural region. It has a very diverse territorial division. In the old division, there are villages, communities, neighborhood housing. In the new one, there are residential condominiums in vertical format, built from the year 2000. This movement in the territory makes the names of places is constantly changing, promoting a shift process, overlap or deletion thereof. Taking this context as a starting point, our work focuses on historical and discursive analysis of place names in urban / rural areas. To understand how Jabotiana consists historically and discursively presented as theoretical framework: the notion of place names from the Great Portuguese and Brazilian Encyclopedia (1960), and the toponymic motivation (DICK, 1990); categories of French Discourse Analysis: interdiscourse subject and discursive formation (Possenti, 2003; (CHARAUDEAU & MAINGUENEAU, 2012; E. ORLANDI 1999); Enunciation as language historical event and the map as text (E.GUIMARÃES, 2002); and the file reading notion (M. PÊCHEUX, 1975) and the historical process of naming names around the "people" and "civilization" (E. BENVENISTE, 1995; J. Starobinski, 2001). For the composition of the corpus, analyze and select different scripts materialities: maps, condos dissemination of advertisements, lists of names of streets and rural and urban locations in Jabotiana in the 2000s, a period in which there is a breakthrough of vertical buildings on site. In the theoretical-methodological process we seek to fundamentally describe historical and discursively the effects of meaning in the appearance, in the reinsertion and the reinterpretation of the appointment in the territory, and how the overlay and / or deletion of different appointments are the Jabotiana so specific.